2014
DOI: 10.1073/pnas.1401013111
|View full text |Cite
|
Sign up to set email alerts
|

Long-term potentiation of glycinergic synapses triggered by interleukin 1β

Abstract: Long-term potentiation (LTP) is a persistent increase in synaptic strength required for many behavioral adaptations, including learning and memory, visual and somatosensory system functional development, and drug addiction. Recent work has suggested a role for LTP-like phenomena in the processing of nociceptive information in the dorsal horn and in the generation of central sensitization during chronic pain states. Whereas LTP of glutamatergic and GABAergic synapses has been characterized throughout the centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 72 publications
4
66
0
Order By: Relevance
“…We found that approximately 10% of IL-1R1 immunostaining on the somatodendritic membrane of neurons was co-localized with gephyrin, a scaffolding protein within the postsynaptic membrane of inhibitory synapses [8688]. In the light of the report of Chirila et al [99], showing that in the superficial spinal dorsal horn glycinergic synapses on inhibitory GABAergic, neurons exhibit LTP, occurring rapidly after exposure to the inflammatory cytokine IL-1β, it is likely that the gephyrin-immunostained spots found to be positive also for IL-1R1 in the present study represent glycinergic synapses. Although we observed IL-1R1 immunostaining only in approximately 1% of gephyrin-immunostained spots, one can regard this finding functionally significant, since the potentiation of glycinergic synapses on GABAergic neurons evoked by in vitro bath application of IL-1β [21, 100] or peripheral inflammation in vivo [99] could evoke considerable disinhibition in pain processing spinal neural networks [21, 101], an important mechanism that is increasingly appreciated for the generation of chronic pain [102, 103].…”
Section: Discussionmentioning
confidence: 99%
“…We found that approximately 10% of IL-1R1 immunostaining on the somatodendritic membrane of neurons was co-localized with gephyrin, a scaffolding protein within the postsynaptic membrane of inhibitory synapses [8688]. In the light of the report of Chirila et al [99], showing that in the superficial spinal dorsal horn glycinergic synapses on inhibitory GABAergic, neurons exhibit LTP, occurring rapidly after exposure to the inflammatory cytokine IL-1β, it is likely that the gephyrin-immunostained spots found to be positive also for IL-1R1 in the present study represent glycinergic synapses. Although we observed IL-1R1 immunostaining only in approximately 1% of gephyrin-immunostained spots, one can regard this finding functionally significant, since the potentiation of glycinergic synapses on GABAergic neurons evoked by in vitro bath application of IL-1β [21, 100] or peripheral inflammation in vivo [99] could evoke considerable disinhibition in pain processing spinal neural networks [21, 101], an important mechanism that is increasingly appreciated for the generation of chronic pain [102, 103].…”
Section: Discussionmentioning
confidence: 99%
“…The impaired morphology, function even death of neurons might be consequences of excessive IL-1b release (Kuhn, 2014). Meanwhile, IL-1b exposure induced LTP in inhibitory GABAergic neurons contributed to somatosensory changes which is another mechanism underlying the development of morphine tolerance (Chirila et al, 2014).…”
Section: Establishment Of Sustained Morphine Incubation Model In Vitromentioning
confidence: 99%
“…Mechanistically, activation of p38 in microglia results in increased synthesis of pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6 (Xu et al, 2013a; Ji and Suter, 2007; Clark et al, 2006; Berta et al, 2014). These cytokines play a critical role in inducing hyperactivity of dorsal horn neurons resulting in pain hypersensitivity (Kawasaki et al, 2008; Ren and Torres, 2009; Zhang et al, 2010; Park et al, 2011; Yan and Weng, 2013; Chirila et al, 2014). Microglial activation was thought to play a role in both sexes (Chen et al, 2012; Cho et al, 2006; Ledeboer et al, 2005), however, it is incompletely known whether p38 signaling in microglia is sex-dependent.…”
Section: Introductionmentioning
confidence: 99%